Dynamic Inflammatory–Immune Biomarker Profiles Associated with Clinical Recovery in Elderly Patients with Severe Pneumonia: A Prospective Study: Inflammatory–Immune Biomarkers in Severe Pneumonia Recovery - Peng, Keling; Qu, Leilei; Zhang, Zirong (Journal of Medical Biochemistry, 2026)
Background: Severe pneumonia in elderly patients is characterized by dysregulated inflammatory responses and impaired immune recovery. However, the dynamic interplay between inflammatory–immune biomarkers and clinical recovery remains insufficiently elucidated from a biochemical perspective. Methods: This prospective study included 276 elderly patients with severe pneumonia. Serial measurements of inflammatory biomarkers [C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6), and neutrophil-to-lymphocyte ratio (NLR)] and immune indicators (CD4+ T cells and natural killer cells) were performed at baseline, day 3, and end-of-treatment. Clinical recovery was evaluated using time to clinical stability, oxygenation index (PaO₂/FiO₂), and length of hospital stay. Associations between biomarker dynamics and recovery outcomes were analyzed. Results: All inflammatory biomarkers exhibited significant declines over time, accompanied by partial restoration of immune function. Greater reductions in CRP, PCT, and IL-6 at early time points were associated with faster clinical stabilization and improved oxygenation (all P < 0.01). NLR showed a pronounced early decrease, reflecting attenuation of systemic inflammatory stress. Notably, recovery of CD4+ T cells was significantly associated with improved clinical outcomes (P = 0.001), suggesting coordinated immune reconstitution. Patients with more favorable biomarker trajectories demonstrated shorter hospitalization and earlier transition to clinical stability. These findings indicate that integrated inflammatory–immune biomarker dynamics closely reflect the biological recovery process in severe pneumonia. Conclusions: Dynamic monitoring of inflammatory and immune biomarkers provides valuable biochemical insights into recovery trajectories in elderly patients with severe pneumonia. Combined biomarker profiling may serve as a practical tool for evaluating disease progression and guiding individualized management strategies.